L-arginine regulates the differential expression of apoptosis genes in gastric cancer cells. Issue 3 (19th December 2022) - Du, Kaining; Han, Jinhong; Shi, Zhexi; Xu, Yilu; Yu, Tingting; Xu, Han; Shu, Xiaoliang
Abstract : Background: According to previous reports, L-arginine may help treat stomach cancer by causing cell apoptosis, but the specific mechanism remains obscure. Objective: The current study aims to discover how L-arginine induces the cell apoptosis in gastric carcinoma. Methods: The cytotoxicity and apoptosis rate of SGC-7901 cells incubated in the RPMI-1640 medium supplemented with L-arginine were detected by CCK8 and flow cytometry. High-throughput RNA-sequencing was performed to search for differentially expressed genes (DEGs). KEGG (Kyoto Encyclopedia of Genes and Genomes) and GO (Gene Ontology) were used to analyze the biological processes and pathways that include the DEGs. Results: In SGC-7901 cells, L-arginine reduced viability in dose- and time-dependent manners. SGC-7901 cells underwent the dose-dependent induction of apoptosis by L-arginine, and the early and late apoptosis rates were 28.33% and 68.2% after 25 mM L-arginine intervention, respectively (both P < 0.0001). The apoptosis-related processes were upregulated, and DNA modification-related processes were downregulated after L-arginine intervention. The hub genes that were significantly increased and decreased after L-arginine incubation were PHLDA1 (pleckstrin homology-like domain family member 1) and DBNL (drebrin-like protein), respectively. Conclusion: Our findings suggested a new treatment target for gastric cancer by demonstrating the enhancement effect of L-arginine on cell apoptosis of gastric cancer.